Exploring the impact of HAp on the surface morphology, mechanical, wettability, and biodegradation rate of PVA-collagen nanofiber bone scaffolds - Hartatiek; M I Wuriantika; W E S Ayu; Yudyanto; S E Rahayu; Nazriati (Materials Research Express)
Nanofibers are considered promising materials for tissue engineering applications due to their ability to promote cell adhesion and form desired environments where new tissue can grow. Furthermore, we evaluated the impact of increasing the concentration (1–6 wt%) of HAp on the morphology and subsequent consequences regarding mechanical properties, wettability, and biodegradative nature of wrinkle-free PVA/collagen nanofiber scaffolds fabricated by electrospinning. FTIR and SEM were used to analyze the functional groups on their surface and observe the morphological characteristics of those particles. SEM revealed that when the concentration of HAp was enhanced, a finer fiber with diameters in the range of 80–500 nm was obtained. The mechanical test demonstrated better mechanical properties of the composites with increasing HAp load. In addition, the water contact angle decreased with increasing HAp concentration (a faster degradation rate), which was consistent with higher suitability degradation.